The Role of Functional Excipients in Solid Oral Dosage Forms to Overcome Poor Drug Dissolution and Bioavailability - Jannes van der Merwe; Jan Steenekamp; Dewald Steyn; Josias Hamman (MDPI AG, 2020)
Many active pharmaceutical ingredients (APIs) exhibit poor solubility and low dissolution rates in aqueous environments such as the luminal fluids of the gastrointestinal tract. The oral bioavailability of these compounds is usually very low as a result of their poor solubility properties. In order to improve the bioavailability of these poorly soluble drugs, formulation strategies have been applied as a means to improve their aqueous solubility and dissolution rates. With respect to formulation approaches, excipients can be incorporated in the formulation to assist in the dissolution process of the drug, or specialized dosage forms can be formulated that improve dissolution rate through various mechanisms. This paper provides an overview of selected excipients (e.g., alkalinizing agents, surfactants and sugars) that can be used in formulations to increase the dissolution rate as well as specialized dosage forms such as self-emulsifying delivery systems and formulation techniques such as inclusion complexes and solid dispersions. These formulation approaches are discussed with available examples with specific reference to positive outcomes in terms of drug solubility and bioavailability enhancement.